GUM KARAYA-G-POLY (ACRYLAMIDE): MICROWAVE ASSISTED SYNTHESIS, OPTIMISATION AND CHARACTERISATION - KAUR, LOVELEENPREET; GUPTA, G. D. (International Journal of Applied Pharmaceutics, 2020)
Objective: The objective of the present research is to formulate acrylamide grafted Karaya gum by using microwave-assisted grafting method and optimisation is performed by using Box behnken design. Methods: The extracted mucilage of gum Karaya was modified into grafted gum Karaya by using a microwave-assisted method. Acrylamide was used as monomer and ceric ammonium nitrate (CAN) is used as redox initiator. The experimental design for optimisation include three independent variables gum concentration (X1), ceric ammonium nitrate (CAN) amount (X2) and irradiation time (X3) while the dependent variables were % yield (Y1), % grafting (Y2) and % grafting efficiency (Y3). The optimised formulation was characterized by fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), x-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis. Results: After optimisation the formulation with acrylamide amount 5 g, ceric ammonium nitrate amount 200 mg and irradiation time of 2 min was selected as optimized formulation. The optimised formulation has percentage grafting of 853.5%, with grafting efficiency of 77.59%. Conclusion: The application of box behnken design for optimisation was performed successfully in microwave assisted grafting of acrylamide on karaya gum.